2019
DOI: 10.1021/acs.orglett.9b01312
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed C═N Bond Formation through a Rebound Hydrolysis Mechanism and Application in β-Lactam Synthesis

Abstract: A rhodium-catalyzed reaction of N-hydroxyanilines with diazo compounds to produce α-imino esters was developed. Distinct from the commonly accepted 1,2-H transfer for normal X−H insertion reactions, density functional theory calculations indicate that this transformation proceeds via a novel rebound hydrolysis mechanism. Furthermore, a three-component reaction was explored to synthesize highly functionalized β-lactams in good yields and diastereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…B3LYP-D3 functional has been widely applied in the theoretical studies on Rh-catalyzed reactions. , To further examine the reliability of our computations with B3LYP-D3­(BJ), we compared the computed overall activation free energies and selectivities with three other popular density functionals, namely, PBE0-D3­(BJ), ,, M06, and ωB97X-D, finding that different functionals exhibited consistent trends (see Supporting Information for details).…”
Section: Methodsmentioning
confidence: 99%
“…B3LYP-D3 functional has been widely applied in the theoretical studies on Rh-catalyzed reactions. , To further examine the reliability of our computations with B3LYP-D3­(BJ), we compared the computed overall activation free energies and selectivities with three other popular density functionals, namely, PBE0-D3­(BJ), ,, M06, and ωB97X-D, finding that different functionals exhibited consistent trends (see Supporting Information for details).…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of Schiff bases can proceed by the condensation reaction of carbonyl compounds with primary amines. Apart from the condensation reaction commonly used in the synthesis of Schiff bases, other synthetic methods have been reported, such as the reductive imination of nitro compounds [3], rebound hydrolysis [4], hydroamination of alkynes with anilines [5], oxidative coupling of alcohols and amines [6] and cross-coupling of amines [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The literature analysis revealed that the overwhelming majority of reported β-lactam syntheses that exploit the disconnection in question involve generating ketenes such as 7 via Rh­(II) carbenes, which, in our view, somewhat tarnishes this approach compared to the convenience and practical simplicity of the catalyst-free Castagnoli–Cushman chemistry. Considering that there are also examples involving thermally and photochemically generated ketenes 7 in the literature, we set off to investigate the feasibility of thermally promoted cyclocondensation of α-acyl-α-diazoacetates 8 with imines as an entry into the β-lactam scaffold.…”
Section: Introductionmentioning
confidence: 99%